2018
DOI: 10.1007/s00784-018-2476-0
|View full text |Cite
|
Sign up to set email alerts
|

Microbial accumulation on different suture materials following oral surgery: a randomized controlled study

Abstract: The study provides the microbial profile of commonly used sutures and may assist in suture selection during clinical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 9 publications
0
40
0
2
Order By: Relevance
“…Asher et al found that bacterial adhesion of coated polyglactin suture was not different from that of other suture materials 7 days after oral surgery. (1) In a clinical study by Sala-Pérez et al, the antibacterial effect of Monocryl Plus suture was observed after 3 days, but this effect was not considerable 7 days after oral surgery. (3) In addition, antibacterial activity of triclosancontaining suture was reported for 96 hours in a study by Edmiston et al and for 12 hours in a study by Masini et al (16,17) Based on previous studies and the results of the present study, it can be concluded that the use of triclosan-coated suture offers no benefit in oral surgery.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Asher et al found that bacterial adhesion of coated polyglactin suture was not different from that of other suture materials 7 days after oral surgery. (1) In a clinical study by Sala-Pérez et al, the antibacterial effect of Monocryl Plus suture was observed after 3 days, but this effect was not considerable 7 days after oral surgery. (3) In addition, antibacterial activity of triclosancontaining suture was reported for 96 hours in a study by Edmiston et al and for 12 hours in a study by Masini et al (16,17) Based on previous studies and the results of the present study, it can be concluded that the use of triclosan-coated suture offers no benefit in oral surgery.…”
Section: Discussionmentioning
confidence: 97%
“…Following the incubation of plates at 37°C for 24 hours, colony-forming units (CFUs) and bacterial growth rates were evaluated. (1,3,13) The sample size was calculated based on previous studies according to power calculations with a 5% alpha error rate. (14,15) A minimum of 20 patients was estimated for statistical significance.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations